A Second Preimage Attack on the XOR Hash Combiner - Shiwei Chen; Ting Cui; Chenhui Jin; Congjun Wang (IET Information Security)
The exclusive-or (XOR) hash combiner is a classical hash function combiner, which is well known as a good PRF and MAC combiner, and is used in practice in TLS versions 1.0 and 1.1. In this work, we analyze the second preimage resistance of the XOR combiner underlying two different narrow-pipe hash functions with weak ideal compression functions. To control simultaneously the behavior of the two different hash functions, we develop a new structure called multicollision-and-double-diamond. Multicollision-and-double-diamond structure is constructed using the idea of meet-in-the-middle technique, combined with Joux’s multicollision and Chen’s inverse-diamond structure. Then based on the multicollision-and-double-diamond structure, we present a second preimage attack on the XOR hash combiner with the time complexity of about O2n+12n/2+n−l2n−l+n−k2n−k+2l+1+2k+1) (n is the size of the XOR hash combiner and l and k are respectively the depths of the two inverse-diamond structures), less than the ideal time complexity O2n, and memory of about O2k+2l.